OPTIMIZING INTRANET NETWORK SYSTEM DESIGN WITH CONTROL PANEL ON USING WINDOWS 95 OPERATING SYSTEM - Andy Pramoedya Soedaryono; Drs. Lingga Hermanto, MM (Jurnal Sistem Komputer, 1998)
Intranet that can bridge all of shape due to the use of network protocols TCP / IP (Transmission Control Protocol / internetworking protocol) is already a standard so that all people are connected in a network can access the Intranet system of systems regardless of type of computer and operating system used. Intranet system can be implemented into a variety of existing network systems such as Novel, Windows, Workgroup and others. And it is also mastering the basics of HTML so that they can create their own homepages that can be displayed on the Intranet server.